The genetics of sporadic ALS: the first Turkish GWAS and novel SNP and CNV association - Uyan, Özgün. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2012., 2012)
Selective degeneration of both lower and upper motor neurons located in the brain cortex, brainstem and ventral horn of the spinal cord result in amyotrophic lateral sclerosis (ALS). ALS is the most frequent late-onset motor neuron disorder and so far no cure or treatment for ALS has been developed. The vast majority of ALS cases are sporadic, approximately 10% of patients have a family history. At least 25 genes and several loci have been identified so far in familial cases. The genetic factors that contribute to ALS correspond to atmost 10% in sporadic cases so there is a huge genetic gap in sALS. The missing part of genetic factors needs to be revealed to fill the lacking players in the mechanisms underlying disease pathogenesis. GWAS enables large scale cohort studies between cases and controls to pinpoint new candidate genomic regions that may be associated with disease phenotype. In the framework of this thesis, we aimed to investigate sporadic ALS patients to identify novel Single Nucleotide Polymorphisms (SNPs), Copy Number Variations (CNVs) and genes, associated with ALS, using GWAS and computational biology approaches. First, we analyzed single marker associations of SNPs in the regions of fALS-causing genes in two published datasets. The ACA haplotype in TARDBP locus was found to be associated with ALS. Next, we performed GWAS on Turkish ALS samples, which included 116 sALS patients and 109 controls. We identified two SNP clusters in TMEM90B and CPNE5 genes associated with ALS, yet all SNPs failed to keep the significance after Bonferroni correction. Third, we performed genome-wide CNV analysis using raw data of GWAS and the PennCNV tool. We identified several novel and reported CNVs in gene and intergenic regions. To the best of our knowledge, this is the first ALS-GWAS of sALS patients in Turkey. We hope that the findings of this thesis in first-stage GWAS and genome-wide CNV analyses will shed light to the unknown genetics of sALS and help to pave the ways in the identification of novel genes associated with sALS pathogenesis.
Keywords: Amyotrophic lateral sclerosis.